Comparison of Maceration and Soxhletation Methods on the Antioxidant Activity of the Bouea macrophylla Griff Plant - Rudiana, Tarso; Nurbayti, Siti; Ashari, Tiara Hadi; Zhorif, Sherina Arestia; Suryani, Nani (Syarif Hidayatullah State Islamic University, 2023)
The impact of extraction methods on the potency of plant extracts is crucial. Bouea macrophylla Griff., a tropical fruit plant rich in phenolic and flavonoid compounds, exhibits strong antioxidant activity. This study aimed to evaluate the effect of maceration and soxhletation extraction techniques on B. macrophylla plants on antioxidant activity in vitro using the method of inhibiting DPPH radical compounds. Ethyl acetate and ethanol solvents were utilized to macerate and soxhlet all parts of the plant. Subsequently, each extract was subjected to quantitative analysis for antioxidant activity, total phenolic, and flavonoid content through UV-Vis spectrophotometry. Quantitative analysis revealed substantial antioxidant activity and notable levels of total phenolic and flavonoid content across all plant parts. The result indicated that although both maceration and soxhletation showed a significant impact on yield (p=0.009) and total flavonoids (p=0.038), significant differences in antioxidant activity (p=0.409) or total phenolics (p=0.874) within the plant extracts of B. macrophylla were not observed at a significance level of 5%.